High APRIL Levels Are Associated With Slow Disease Progression and Low Immune Activation in Chronic HIV-1-Infected Patients - Liu, Yubin; Li, Xiuxia; Han, Yang; Qiu, Zhifeng; Song, Xiaojing; Li, Bingxiang; Zhang, Han; Wang, Hongye; Feng, Kai; Liu, Longding; Wang, Jingjing; Sun, Ming; et al. (Frontiers in Medicine, 2020)
Objective: B-cell-activating factor (BAFF) has been determined to be involved in HIV-1 infection and correlate with disease progression, while its homologous molecule, a proliferation-inducing ligand (APRIL), is less frequently reported, and its role remains unclear. We aimed to characterize APRIL levels in subjects with different HIV-1 infection statuses and determine the relationships with disease progression and immune activation. Methods: Plasma levels of APRIL were compared in 17 long-term nonprogressors (LTNPs), 17 typical progressors (TPs), 10 ART-treated patients and 10 healthy donors (HDs). Seventeen LTNPs and a subset of TPs (n=6) who initiated ART were assessed longitudinally. Correlation of APRIL levels with markers of disease progression, B-cell count and specific antibody response, markers of immune activation and functional cells were analyzed. Results: Circulating APRIL levels were significantly elevated in LTNPs relative to TPs, ART-treated patients and HDs. Longitudinal investigation revealed that APRIL levels decreased during follow-up in LTNPs. ART did not significantly influence APRIL levels. The levels of plasma APRIL were negatively correlated with plasma HIV-1 viral load and cellular HIV-1 DNA levels and positively correlated with CD4+T-cell count and CD4/CD8 ratio. The inverse correlation was observed between APRIL and BAFF levels. Furthermore, APRIL levels were negatively correlated with the frequency of activated CD8+T cells and levels of IP-10 and MCP-1. Lastly, positive correlations were observed between APRIL levels, the frequency of CD8+CD28+T cells and natural killer (NK)-cell count. Conclusion: APRIL levels were elevated in LTNPs and negatively correlated with disease progression and immune activation, indicating a likely protective activity in HIV-1 infection.